2021
DOI: 10.3390/min11060592
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Mechanical Characteristics and Microstructure of Cemented Whole Tailings Backfill

Abstract: A paste backfill performance can be primarily evaluated through the mechanical and physical characteristics of the components involved. In this study, the effects of solid components’ tailings, binders and waters contents on microstructural evolution and mechanical properties of uncemented whole tailings backfill (CWTB) mixtures were investigated. Different mixtures of ordinary Portland cement of 1, 3 and 5 wt. % and solid concentrations at 72 wt. %, 74 wt. % and 75 wt. % were selected and rheological test was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…The above studies mainly focused on the complete filling body, and with the consumption of external mineral resources, deep mining has gradually become the mainstream mining trend [22,23]. The development of deep mining technology is accompanied by the rapid increase in the number and size of goaf [24][25][26][27][28][29]. Limited by the current domestic filling technology, it is almost impossible to fill large-scale mined-out areas once, which leads to the stratification of the filling body due to layer-by-layer filling [30][31][32][33].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The above studies mainly focused on the complete filling body, and with the consumption of external mineral resources, deep mining has gradually become the mainstream mining trend [22,23]. The development of deep mining technology is accompanied by the rapid increase in the number and size of goaf [24][25][26][27][28][29]. Limited by the current domestic filling technology, it is almost impossible to fill large-scale mined-out areas once, which leads to the stratification of the filling body due to layer-by-layer filling [30][31][32][33].…”
Section: Methodsmentioning
confidence: 99%
“…Mining is one of the essential conditions to ensure the rapid development of China’s economy, but mining also brings problems such as goaf collapse and mining waste pollution [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. The filling mining method can effectively control stope ground pressure and stope deformation while making full use of mine solid waste tailings, which not only ensures the safety of mining but also solves the problem of environmental pollution to a certain extent [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ], so it is extensive use of various metal and non-metal mines.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the high molecular polymer PAM molecules connected and interacted with TS and OPC particles by the formation of floc and the bridging effect in CPB mixtures [17]. These floc formed between particles not only enhance the viscosity of fresh CPB mixtures but also increase the mechanical strength of hardened CPB specimens [13]. As shown in Figure 6, the morphologies of hydrates including C-S-H, ettringite, and CH are more relevant to W/S ratios rather than the chemical additives.…”
Section: Microstructurementioning
confidence: 99%
“…Li et al [12] used response surface methodology to systematically investigate and illustrate that fly ash, silica fume, sand to binder ratio and water to binder ratio and their partial interactions have remarkable effects on the rheological and mechanical performances of self-compacting mortars, especially the silica fume and sand to binder ratio. In addition, Belibi Tana et al [13] have shown the yield stress and slump value of uncemented whole tailings backfill paste slurries were positively correlated, and that increasing the solids content would affect their porosity and enhances their strength resistance. Libre et al [14] investigated the effect of chemical and mineral admixtures on the fluidity, viscosity, and stability of self-compacting mortars at different water/cement ratios, and proposed suitable workability zones for formulating mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…These mine tailings usually contain hazardous chemical compounds and would otherwise be impounded on the land posing a grave threat to the environment as well as human lives. In addition, the CPB technology is economically advantageous because it improves the productivity of ore retrieval during mining [1][2][3][4][5][6]. Moreover, binder inclusion ensures that the backfill becomes self-supporting after a short period, making the excavation of adjacent ore body possible.…”
Section: Introductionmentioning
confidence: 99%